Metamodernism: A Multispecies Approach to Hermeneutics - Nencini, Andrea Maria (Method & theory in the study of religion, 2025)
This paper discusses the merits of the multispecies approach, presented by Jason Ā. Josephson Storm, in his book Metamodernism. By offering a compelling analysis of the causes that led human sciences to fall into the opposition between ontological and mind-dependent interpretation of phenomena, Josephson Storm attempts to solve the resulting impasse by examining how hermeneutical processes result from an active dialectical relation between living organisms and the contextual regularities the environment offers them. Thanks to its capacity to prevent essentialism, while at the same time allowing a form of a relational and pragmatic ontology of the ‘objects’ under research scrutiny, I argue that this method of analysis of social categories can represent a valuable tool for scholars of religion.